Proton‐Conducting Fuel Cells: A New Pd Doped Proton Conducting Perovskite Oxide with Multiple Functionalities for Efficient and Stable Power Generation from Ammonia at Reduced Temperatures (Adv. Energy Mater. 19/2021). Issue 19 (20th May 2021) - He, Fan; Gao, Qinning; Liu, Zuoqing; Yang, Meiting; Ran, Ran; Yang, Guangming; Wang, Wei; Zhou, Wei; Shao, Zongping
Abstract : In article number 2003916, Guangming Yang, Zongping Shao and co‐workers investigate a new Pd doped BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3−δ as an anode component and electrolyte, which boosts the activity of anodes for NH3 decomposition, and increases proton conductivity and sintering of electrolytes. The NH3 ‐fueled proton‐conducting fuel cell delivers superior power density and stability, making it highly promising for practical applications.